2017
DOI: 10.1002/jcb.26320
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin ameliorates LPS‐induced inflammatory response by autophagy via AKT/mTOR signaling pathway

Abstract: Macrophages play crucial roles in immune response and atherosclerosis-related cardiovascular disease. Recent evidence of macrophage autophagy has demonstrated a novel pathway through which contributes to vascular inflammation. The aim of this study was to elucidate the role of autophagy in the inhibition of inflammatory response in macrophages by atorvastatin. We found that atorvastatin promoted autophagy flow determined by up-regulating the expression of autophagy-related protein microtubule-associated protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…suggesting that M1 microglia are increased in AIS patients. We also found that the expression of miR30d-5p was decreased, which is related to autophagy regulation, while autophagy is related to the inflammatory response [42,43]. The results show that miR-30d-5p can significantly suppress ischemia-induced autophagy by targeting both Beclin-1 and Atg5.…”
Section: Discussionmentioning
confidence: 61%
“…suggesting that M1 microglia are increased in AIS patients. We also found that the expression of miR30d-5p was decreased, which is related to autophagy regulation, while autophagy is related to the inflammatory response [42,43]. The results show that miR-30d-5p can significantly suppress ischemia-induced autophagy by targeting both Beclin-1 and Atg5.…”
Section: Discussionmentioning
confidence: 61%
“…These results indicated that overexpression of miR‐29a activated the AKT/mTOR signalling pathway by inhibiting PTEN during cardiac hypertrophy. Notably, mTOR is recognized as a negative regulatory factor of autophagy, and the AKT/mTOR pathway is known to regulate autophagy; we thus examined autophagy in pathological cardiac hypertrophy. By transmission electron microscopy, we observed that the number of autophagic vacuoles and autophagosomes in the ventricular septal tissue of TAC‐operated rats was reduced (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, LPS‐induced inflammation was closely related to autophagy, which contributed to cell survival and downregulated the production of proinflammatory cytokines (Bussi et al, ; Zeng et al, ). Knockdown of ATG5 with siRNA prevented the role of atorvastatin in decreasing interleukin‐1β and tumor necrosis factor‐α release induced by LPS (Han et al, ). Our results demonstrated that UCA1 was positively correlated with autophagy markers LC3 and inversely correlated with AKT and mTOR after LPS‐induced 4–6 hr in 293T cells.…”
Section: Discussionmentioning
confidence: 99%